Understanding Online Gaming Habits and Attitudes among Youth: A FGD Study of Gaming Behaviours, Social Interactions, and Psychological Effects - Loh Yoke Ling, Ahmad Sauffiyan Bin Abu Hasan (Tanjung Malim, 2024)
Understanding Online Gaming Habits and Attitudes among Youth: A FGD Study of Gaming Behaviours, Social Interactions, and Psychological Effects by Loh Yoke Ling, Ahmad Sauffiyan Bin Abu Hasan